The Genetic Architecture of Behavioral Disorders: Exploring the Role of Epigenetics in Psychiatry - Eskandar, Kirolos (Psychotherapie-Wissenschaft, 2025)
Behavioral disorders such as depression, schizophrenia, ADHD, and autism spectrum disorders represent a significant challenge in psychiatry due to their complex and multifactorial nature. While traditional models have focused on genetic predispositions, emerging research highlights the critical role of epigenetics in modulating gene expression in response to environmental factors. This literature review explores the genetic architecture of behavioral disorders, emphasizing the influence of epigenetic mechanisms such as DNA methylation, histone modification, and non-coding RNAs. We delve into how these processes contribute to the onset, progression, and transgenerational transmission of psychiatric conditions. Furthermore, we discuss the implications of these findings for personalized treatment strategies and future research directions, underscoring the potential for epigenetic therapies in reshaping psychiatric practice. This review aims to bridge the gap between genetics and environment, offering a comprehensive understanding of how epigenetics can inform the future of psychiatric care.